Macroeconomics As A Determinant Of Demand For Oil And Gas Exports And Non-oil And Gas In East Nusa Tenggara Region By Timor Leste - Perseveranda, M. E; Adrianus Ketmoen; Indrawati, Agnes Susanti; Maria Imakulata Pongge; Enike Tje Yustin Dima (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
International trade is a key component in enhancing welfare and economic growth, as well as generating foreign exchange needed for development. East Nusa Tenggara (NTT), with its significant potential in the oil and gas, as well as non-oil and gas sectors, has considerable export opportunities to Timor Leste. However, the effectiveness of NTT's exports is heavily influenced by various macroeconomic factors, such as exchange rates, per capita income, and government spending in both Indonesia and Timor Leste. The variation in resources and production capacity in NTT offers opportunities to meet Timor Leste's demand, but changes in macroeconomic conditions play a critical role in determining the competitiveness of NTT's export products. This study employs a quantitative approach with multiple linear regression analysis to examine the impact of macroeconomic variables on the demand for oil and gas, as well as non-oil and gas exports from NTT to Timor Leste. The sample used consists of annual time series data from 2021 to 2023, including the Rupiah exchange rate against the US Dollar, Timor Leste's per capita income, and government spending in Timor Leste. The results show that the exchange rate has a significant negative impact on export demand, while government spending has a positive effect. Timor Leste's per capita income does not significantly affect export demand. These findings are expected to contribute to policymakers in improving NTT's export competitiveness and volume, ultimately having a positive impact on the region's economic welfare.ipsum